Morphological and SSR marker analysis for genetic diversity assessment in galgal (Citrus pseudolimon Tanaka) germplasm - Thirugnanavel, A; Prasanth , T K J; Ashutosh , A M; Jitendra, U K; Prafulla , R J; Snehal , A K; Chaitanya, P D (Plant Science Today, 2025)
Galgal (hill lemon or Himalayan lemon), an indigenous and drought-tolerant species widely grown across Himalayan states, is renowned for its culinary use in pickles and beverages. Despite its utility, galgal remains underutilized, necessitating comprehensive studies on its genetic and phenotypic diversity. This study investigated the genetic diversity of 13 Indigenous galgal germplasm maintained at the ICAR-Central Citrus Research Institute, Nagpur, using 21 morphological traits and 46 simple sequence repeat (SSR) markers. The study demonstrated the ability to select germplasm for breeding by the highest phenotypic and genotypic coefficients of variation for traits like seed number (61.35 % and 60.57 %), canopy volume (53.33 % and 53.29 %) and rind thickness (45.92 % and 45.49 %). High heritability (>80 %) and genetic advance for characters like canopy volume, fruit weight and rind thickness suggest the predominance of additive gene action, making them ideal targets for improvement. Principal component analysis (PCA) identified seven components explaining 92.3 % of the variability, with fruit and plant traits contributing the most. Cluster analysis grouped the germplasm into three clusters based on morphological characteristics. Molecular characterization using 46 SSR markers showed distinct germplasm with polymorphism information content (PIC) values ranging from 0.260 to 0.698, averaging 0.4851. UPGMA dendrogram and principal coordinate analysis (PCoA) clustered the germplasm into two major groups. The results of the morphological and molecular markers revealed a rich genetic diversity of galgal. The germplasm present in the single cluster should be avoided in breeding. The traits responsible for genetic variation in galgal germplasm should be considered for galgal improvement programmes.